1981
DOI: 10.1007/bf00431111
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary double-blind study on the efficacy of carbamazepine in prophylaxis of manic-depressive illness

Abstract: A preliminary double-blind controlled study on the prophylactic effect of carbamazepine on recurrent manic-depressive psychotics was conducted with 22 patients using an inert placebo in ten subjects as a control drug. Carbamazepine in the dosage of 200-600 mg was administered for 1 year. Among the 22 carbamazepine subjects, carbamazepine was found to be effective in 60% of the cases and inert placebo in 22.2% (U-test, P less than 0.10). It is suggested that carbamazepine is a useful drug for the prophylaxis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(75 citation statements)
references
References 2 publications
2
73
0
Order By: Relevance
“…3] in 90 cases, and it was found that CBZ had antimanie and pro phylactic effects for bipolar disorder. The antimanie ef fect was confirmed by double-blind studies by Okuma et al [4,5] and by Ballengcr and Post [6,7], and the prophy lactic effect in a double-blind study by Okuma et al [8], Following these observations, the effects of CBZ on bipo lar disorder have been confirmed by many researchers throughout the world [9,10], and the therapeutic and pro-phylactic effects of CBZ are almost established at the present time.…”
Section: Introductionsupporting
confidence: 62%
“…3] in 90 cases, and it was found that CBZ had antimanie and pro phylactic effects for bipolar disorder. The antimanie ef fect was confirmed by double-blind studies by Okuma et al [4,5] and by Ballengcr and Post [6,7], and the prophy lactic effect in a double-blind study by Okuma et al [8], Following these observations, the effects of CBZ on bipo lar disorder have been confirmed by many researchers throughout the world [9,10], and the therapeutic and pro-phylactic effects of CBZ are almost established at the present time.…”
Section: Introductionsupporting
confidence: 62%
“…Most studies found it to be comparable to lithium in effectiveness, except for three studies (Okuma et al 1981;Lerer et al 1987;Watkins et al 1987). However, for prophylactic treatment, according to a recent meta-analysis of this literature (Dardennes et al 1995), the effectiveness of carbamazepine remains to be established.…”
Section: Carbamazepinementioning
confidence: 99%
“…double-blind controlled trial showing prophylacti c e ffec ts of ca r bamazepine in 60 % and placebo in 22.2% of their patients (V-test, p < 0.10) ( 17). Kishimoto et at.…”
Section: Dr Pate Is a Third-year Residen T At Baylor College Ofmedicmentioning
confidence: 99%